An evaluation of diets in the Polish national judo team during the pre-competition weight loss period - Ksiazek, A.; Karpala, J.; Slowinska-Lisowska, M. (Archives of Budo, 2017)
Background and Study Aim: Diets of professional athletes, especially during the pre-competition weight reduction period, may have a significant impact on the sport results and the athletes` health. The aim of the study was the energy value and the intakes of nutrients, minerals, vitamins, dietary fibre and water in daily food rations in the representatives of the Polish national judo team during the pre-competition weight loss period.